2012
DOI: 10.1152/ajpheart.00362.2012
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective proteins upregulated in the liver in response to experimental myocardial ischemia

Abstract: Myocardial ischemia (MI) activates innate cardioprotective mechanisms, enhancing cardiomyocyte tolerance to ischemia. Here, we report a MI-activated liver-dependent mechanism for myocardial protection. In response to MI in the mouse, hepatocytes exhibited 6- to 19-fold upregulation of genes encoding secretory proteins, including α-1-acid glycoprotein (AGP)2, bone morphogenetic protein-binding endothelial regulator (BMPER), chemokine (C-X-C motif) ligand 13, fibroblast growth factor (FGF)21, neuregulin (NRG)4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
3
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(108 citation statements)
references
References 68 publications
4
95
3
5
Order By: Relevance
“…Elevating the adenosine level in the heart causes vasodilation and an increase in heart rate (33). Adenosine has been implicated in the initial injury process, because it is a well-known signaling molecule for stress and tissue injury (34)(35)(36). From this study, we observed a gradual increase in the adenosine deaminase transcript level (peaking in the T3R1 group).…”
Section: Discussionmentioning
confidence: 51%
“…Elevating the adenosine level in the heart causes vasodilation and an increase in heart rate (33). Adenosine has been implicated in the initial injury process, because it is a well-known signaling molecule for stress and tissue injury (34)(35)(36). From this study, we observed a gradual increase in the adenosine deaminase transcript level (peaking in the T3R1 group).…”
Section: Discussionmentioning
confidence: 51%
“…Several growth, paracrine, and autocrine factors are released by stem cells if/when they arrive at the site of injury. 20 sCBSCs, CDCs, and MSCs all showed chemotaxis for most of the paracrine factors, including bFGF, HGF, VEGF, IGF-1, stromal-derived growth factor 1, platelet-derived growth factor, and TGF-β. CBSCs showed increased migration toward TGF-β compared with CDCs and MSCs (CBSCs versus CDCs and MSCs; P<0.001; Figure 2G).…”
Section: Morphology and Growth Kinetics Of Cbscsmentioning
confidence: 99%
“…2 pCBSCs, CDCs, and MSCs were plated in a 6-well dish (30 000 cells/well) and incubated in their respective medium without serum overnight and then treated with 10,20,30,40, and 50 μmol/L H 2 O 2 overnight. Cell death was confirmed by visualizing the cells under a light microscope before collection.…”
Section: Proliferation and Survival Assaysmentioning
confidence: 99%
“…This may at first seem counterintuitive as proteins up-regulated in disease tend to serve a pathologic role. However, the scientific literature catalogues a growing number of proteins up-regulated in disease that work to counter the disease process, reestablish homeostasis, and return the body to its original state of health (61)(62)(63), and we have found that FAP behaves in such a fashion in pulmonary fibrosis. This study is the first to demonstrate that the absence of FAP worsens the development of pulmonary fibrosis after lung injury, establishing a protective role for FAP in the lung.…”
Section: Discussionmentioning
confidence: 90%